Implementation of Government Policies in an Effort to Increase Malino Tourism Through the Beautiful Malino Event in Gowa Regency - Aslinda, Andi; Cahyanti, Nur Dwika; Akib, Haedar (Universitas Negeri Makassar, 2024)
This study aims to produce an accurate picture of the implementation of government policies in an effort to increase malino tourism through beautiful malino events in Gowa Regency as well as supporting and inhibiting factors in the implementation of government policies in an effort to increase malino tourism through beautiful malino events in Gowa Regency. This type of research is descriptive qualitative research with data collection techniques, namely interviews, observations, and documentation. The validity of the data is checked through source triangulation. Data analysis techniques use data condensation, data presentation, and conclusions. The results showed that the implementation of government policies in an effort to increase malino tourism through beautiful malino events in Gowa Regency has been carried out well and runs according to theory. This can be seen from the theory of George C. Edwards III which is used to describe and explain the implementation of government policies in terms of communication, resources, dispositions and bureaucratic structures.